MANGKAT ONAK Studi Mengenai Tradisi Angkat Anak di Kalangan Orang Dayak Desa di Dusun Landau, Meliau, Kalimantan Barat - , PINDHO ADIYAKSA, Dr. Pujo Semedi Hargo Yuwono, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Most of the Dayak Desa people in Landau Village, used to be farmers in swidden agriculture. The goal was to fulfill their daily needs (subsistent). In swidden agriculture, they sufficed their labor through kinship ties. If it was insufficient, they could fulfill their labor through labor exchange system. Currently, the system has changed since the introduction of new commodities such as rubber and palm oil. This transformation give an effect to the mode of production among them. It can be seen through the changing in labor compliance . Labor system which is based on kinship and reciprocity norms have already changed to be labor hired. This phenomenon shows up because of the cash needs among the residents. The increasing of cash needs was influenced by many factors. The main factor impacting that phenomenon was the market effect. The Dayak Desa people commonly have integrating to the market. In this final thesis, I attempt to figure out why a ritual tradition of foster child is still conducted continuously by Dayak Desa people even though they have been modern societies. Surprisingly, the ritual is only implemented by specific a group of societies such as farmers or common residents. However, the tokeh who is categorized to rich people prefers not to adopt children. In fact, the ritual has been used by common farmers to consolidate the social network. A strong social network intend to build the powerful social capital. The common farmers who do not have enough capital usually take the advantage of their social capital to be able to survive in the competitive economic system. Therefore, the social economic relation among the farmers which is more transactional can be negotiated in order to be more personal. The foster child ritual can be seen as an instrument to promote the economic base residents in the middle of the economic system transformation. This research conducted in Landa village, Melawi Makmur, Meliau subdistrict, Sanggau District, Kalimantan Barat. Most of the Landauâs residents are Dayak Desa people who mostly work in the plantation sector.